P71 Neurosurgical presentation of hereditary transthyretin (ATTR) amyloidosis: early recognition for earlier genetic therapies. Issue 3 (14th February 2019) - Kapoor, M; Quaegebeur, Annelies; Shah, Sachit; Carr, AS; Reilly, MM
Abstract : Objectives: Hereditary Transthyretin (ATTR) amyloidosis is a genetic disorder where insoluble amyloid fibrils deposit in heart, nerves and various musculoskeletal tissues. Early recognition of TTR-FAP is important as new genetic therapies become available. Design: We present one confirmed and one clinical case of ATTR deposition in ligamentum flavum causing lumbar canal stenosis. Subjects: The first case is a 44-year-old female with TTR 184S heterozygous mutation who developed urinary urgency and bilateral leg pain exacerbated by walking. Neurological examination was normal. MRI lumbar spine showed a disc bulge in combination with ligamentum flavum thickening at L2/3 causing stenosis of the vertebral canal. She had a laminectomy of the L2/3 level. Histopathological analysis of the surgical tissue was positive on Congo red staining for amyloid and immunohistochemically identified as TTR type. The second case is a 68-year-old man with TTR V122I heterozygous mutation. He presented with paraesthesia from the knees to dorsum of the feet. On examination, power was normal and he had a length dependent neuropathy. A CT myelogram demonstrated spondylosis at L4/5 and L3/4 from disc bulge and marked flaval hypertrophy causing canal stenosis. He was placed on the waitlist for L4-5 decompression but unfortunately died prior to surgery. Conclusions: Identifying ATTR in surgical specimens may diagnose hereditary amyloidosis in otherwise asymptomatic patients and in the future, provide early access to effective therapies.